Incomplete descriptions and indistinguishable participants - Elbourne, P (Springer Netherlands, 2015)
The implicit content associated with incomplete definite descriptions is contributed in the form of definite descriptions of situations. A definite description of this kind is contributed by a small structure in the syntax, which is interpreted, in general terms, as ‘the situation that bears R to s’.